The white death: silicosis (miner's phthisis) on the Witwatersrand gold mines 1886-1910 - Katz, Elaine N (My University, 1990)
In its chronic form silicosis had always been been taken for granted as one of the occupational hazards of mining. But both during and shortly after the Anglo-Boer War it manifested itself in a new accelerated form amongst former Witwatersrand rock drillers. Despite the appointment in the Transvaal of a commission of enquiry in 1902 and the promulgation of dust precaution measures, by 1912 the prevalence of and mortality from the disease amongst the Witwatersrand miners had not diminished. This finding suggests two of the purposes of the study: first, the reasons for the continued prevalence of the disease; and second, the extent of the mortality from silicosis amongst the miners. Because of the apparently low prevalence of and mortality from the disease amongst African mineworkers, the disease was ironically nick-named the "white death". Therefore another aim of the study is to examine the validity of the medical claim that the short contracts of African migrant workers safeguarded them from contracting accelerated si licosis. As the subject is complex, the study uses a thematic approach. Chapters two to nine deal with significant themes: first, the growing medical knowledge concerning silicosis, the mining and medical precautions against the disease and the age-old disregard for the occupational illness in its chronic form; second, the industrialists* need to reduce working costs, the development of mass-production technologies and the resort by management to "speeding up"; and third, the miners' needs for job and wage security, the encroachment of African competitors in semi-skilled and skilled spheres of mining and the introduction and the extension of the colour bar. Chapter nine deals with underground health conditions. Chapter ten explores the awareness of the new form of the disease, accelerated silicosis, and the establishment in 1902 of the first Transvaal commission on silicosis. Chapter eleven discusses the failure to implement remedies. Finally, chapter twelve explores the prevalence of and mortality from silicosis and the impact of the disease on the workforce of the mines. In chapters ten, eleven and twelve a synthesis is offered of the themes and findings of the previous chapters. The project is based almost entirely on contemporary primary and published sources. Apart from silicosis, a unifying theme throughout the discrete sections is the perceptions of miners of their vocation in general, and of this occupational disease in particular. The study requires periodization. As silicosis is a slow-developing disease the starting point of the investigation is 1886, when gold was discovered on the Rand. The study ends in 1910 because the establishment of Union in 1910 and the legal award of compensation in 1911 heralded a new era in the history of silicosis on the South African gold mines. The following are the conclusions. First, almost an entire generation of overseas miners, most of whom remained migrants and whose skills pioneered the South African gold mining industry, died from silicosis. Second, for reasons of self-interest, some of which they shared with one another, both the Transvaal state and the Randlords did virtually nothing to remedy the occurrence of the disease. Both parties were culpable for the neglect of the health of the industry's workforce: using only perfunctory dust safeguards, management intensified production through the deployment of both modern technology and labour intensive practices, peculiar to the Witwatersrand; and most of the state's interventionist initiatives were the result of pressure from the British House of Commons. Third, the fear and anger of miners at being the victims of a preventable occupational disease, provided the catalyst for their militancy during the period. Fourth, the industry's power was partly responsible for causing both the press and medical profession to be silent about the problem until 1910. Finally, the mineowners both seized and promoted the unsubstantiated medical orthodoxy, namely that the short contracts of African mineworkers protected them from accelerated silicosis, as an important rationale for perpetuating the migrant labour system
A THESIS SUBMITTED TO THE FACULTY OF ARTS, UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG, IN FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF DOCTOR OF PHILOSOPHY.
Keywords: Silicosis -- South Africa -- Witwatersrand.; Gold mines and mining -- South Africa.; Miners' phthisis -- South Africa -- Witwatersrand.; Miners -- Diseases.; Mineral industries -- South Africa -- Witwatersrand -- Employees -- Diseases.